2015
DOI: 10.4012/dmj.2014-178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flowability on the flow rate, polymerization shrinkage, and mass change of flowable composites

Abstract: As a lining or restoration material, flowable composites are popular due to their ease in use and agreeable marginal adaptation of tooth cavity. The purpose of the present study was to evaluate various properties of flowable composites which were claimed to be of high or low flowability by the manufacturers. For the study, twelve flowable composites from six different manufacturers were used. Based on the manufacturers' claim, they were divided into two groups: high or low flowability. The products grouped in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Ku et al, investigated 12 flowable composites from six manufacturers, divided into groups of high or low flowability, according to the manufacturers’ claim. Those of high flowability showed significantly higher polymerization shrinkage, regardless of the light-curing unit used [ 35 ]. In another study, the incremental filling with a flowable composite liner showed higher spot deflection than that without a flowable liner, and the difference was maintained until 2000 s after the initiation of light curing.…”
Section: Development Of Discussionmentioning
confidence: 99%
“…Ku et al, investigated 12 flowable composites from six manufacturers, divided into groups of high or low flowability, according to the manufacturers’ claim. Those of high flowability showed significantly higher polymerization shrinkage, regardless of the light-curing unit used [ 35 ]. In another study, the incremental filling with a flowable composite liner showed higher spot deflection than that without a flowable liner, and the difference was maintained until 2000 s after the initiation of light curing.…”
Section: Development Of Discussionmentioning
confidence: 99%
“…The reason for non-linear correlation between filler content and polymerization shrinkage is not clear. Ku et al reported that polymerization shrinkage was less correlated with filler content for commercially available flowable resins 9) . It is well known that the degree of photo polymerization of photo-curable composite resins depends on the differences of refractive indexes, kinds of monomers or fillers, shape and distribution of fillers and photo polymerization initiators, etc., besides filler content.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of filler content in flowable resin composite is limited in order to maintain its flowability. This decrease of inorganic filler content corresponds with an increase of monomer content, leading to the increase of polymerization shrinkage 9) . The occurrence of polymerization shrinkage in a restoration can lead to secondary caries, pulpal damage, and debonding of restorative appliances due to gap formation between restorative materials and cavity walls.…”
Section: Introductionmentioning
confidence: 99%
“…Bununla birlikte, bir akışkanlık derecesi olarak akış hızının uygulanan ışık kaynağı ve polimerizasyondan bağımsız olarak mikrosertlik, polimerizasyon büzülmesi, su emme ve çözünürlüğü ile düşük korelasyona sahip olduğu bildirilmiştir. 82…”
Section: Akıcı Kompozit Rezinlerde Akış/akışkanlıkunclassified